2007
DOI: 10.1017/s1743921308015895
|View full text |Cite
|
Sign up to set email alerts
|

Central Dynamics of Globular Clusters: the Case for a Black Hole in ω Centauri

Abstract: Abstract. The globular cluster ω Centauri is one of the largest and most massive members of the Galactic system. Its classification as a globular cluster has been challenged making it a candidate for being the stripped core of an accreted dwarf galaxy; this and the fact that it has one of the largest velocity dispersions for star clusters in our galaxy makes it an interesting candidate for harboring an intermediate mass black hole. We measure the surface brightness profile from integrated light on an HST /ACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
1
0
1
Order By: Relevance
“…A single or binary IMBH could account for the net rotation observed in the center of M15 (Gebhardt et al 2000;Gerssen et al 2002;Miller & Colbert 2004;Kiselev et al 2008). Maccarone & Servillat (2008) shows the possible presence of an IMBH in NGC 2808 with a mass of ∼ 2.7 × 10 3 M⊙ and Noyola et al (2008) have reported about the BH in omegaCen with a mass of ∼ 10 4 M⊙ . However, Baumgardt et al (2003) have shown through selfconsistent N -body computations treating stellar evolution and with a realistic IMF, that the core collapse profile of a star cluster with an unseen concentration of neutron stars and heavy-mass white dwarfs can explain the observed central rise of the mass-to-light ratio (see also McNamara et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…A single or binary IMBH could account for the net rotation observed in the center of M15 (Gebhardt et al 2000;Gerssen et al 2002;Miller & Colbert 2004;Kiselev et al 2008). Maccarone & Servillat (2008) shows the possible presence of an IMBH in NGC 2808 with a mass of ∼ 2.7 × 10 3 M⊙ and Noyola et al (2008) have reported about the BH in omegaCen with a mass of ∼ 10 4 M⊙ . However, Baumgardt et al (2003) have shown through selfconsistent N -body computations treating stellar evolution and with a realistic IMF, that the core collapse profile of a star cluster with an unseen concentration of neutron stars and heavy-mass white dwarfs can explain the observed central rise of the mass-to-light ratio (see also McNamara et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Οι ολικές ταχύτητες δεν είναι παρατηρησιακά διαθέσιμές, κάτι που εισάγει επιπλέον περιορισμούς στον ακριβή υπολογισμό της ενδεχόμενης ΙΜΒΗ. Χρησιμοποιώντας διαφορετικές προσεγγίσεις των παρατηρήσεων οι van der Marel & Anderson (2010) [53], βρήκαν πως το άνω όριο της μάζας της ΙΜΒΗ που μπορεί να βρίσκεται στο κέντρο του ω-Centauri, είναι 1.2×10 4 M , ενώ εντόπισαν ένα σφάλμα της τάξης των 12arcsec στον προσδιορισμό του κέντρου του σμήνους στους υπολογισμούς των [50]. Σύμφωνα με ακόμη πιο πρόσφατες μελέτες [54], η μάζα της συγκεκριμένης υποθετικής ΙΜΒΗ είναι 4.7 ± 1.0 × 10 4 M .…”
Section: παρατήρησεις οξέως άκρου στην κεντρική πυκνότητα και την ταχύτητα διασποράς σφαιρωτών σμηνώνunclassified